Old Testament theology ; v. 2 - von Rad, Gerhard, 1901-1971; Stalker, David M.G. (Louisville, KN Westminster, 2002)
Contents : v. 2 :The theology of Irael's prophetic traditions. Includes bibliographical references and indexes.
A translation of Theologie des Alten Testamnts, Bd II, Die Theologie der prophetischen Uberlieferungen Israels, Published by Chr Kaiser Verlag, Munich, 1960
Keywords: Bible. O.T. -- theology